Perancangan Pembangkit Listrik Tenaga Deisel (PLTD) di Merauke - Sukayo Sukayo; Anton Topan; Sari Octavia (Musamus Journal of Architecture, 2020)
The Diesel Power Plant (PLTD) currently used in Merauke has a capacity of only 12.6 MW, while the peak load reaches 17.39 MW, resulting in frequent power outages in Merauke Regency. Additionally, the location of PLTD Kelapa V in the city center causes significant noise pollution, disturbing nearby residents. To address these issues, a new PLTD with a capacity of 100 MW is needed in the warehouse and industrial sector, utilizing a techno-architecture design approach. This research employs data collection methods such as interviews, documentation, books, reports, literature studies, journals, site analysis, and building analysis. The result of this study is the design of a diesel power plant with a techno-architecture approach that can enhance the power and performance capacity of PLTD Kelapa V, ensuring adequate electricity supply for Merauke.